DNA methylation predicts age and provides insight into exceptional longevity of bats - Gerald S. Wilkinson (Nature Portfolio, 2021)
DNA methylation profiles from 26 bat species accurately predicts chronological age, while longevity-related methylation patterns across the genome suggest that bat longevity results from augmented immune response and cancer suppression.